Role of arginase 1 from myeloid cells in th2-dominated lung inflammation. - Luke Barron; Amber M Smith; Karim C El Kasmi; Joseph E Qualls; Xiaozhu Huang; Allen Cheever; Lee A Borthwick; Mark S Wilson; Peter J Murray; Thomas A Wynn (PLoS ONE)
Th2-driven lung inflammation increases Arginase 1 (Arg1) expression in alternatively-activated macrophages (AAMs). AAMs modulate T cell and wound healing responses and Arg1 might contribute to asthma pathogenesis by inhibiting nitric oxide production, regulating fibrosis, modulating arginine metabolism and restricting T cell proliferation. We used mice lacking Arg1 in myeloid cells to investigate the contribution of Arg1 to lung inflammation and pathophysiology. In six model systems encompassing acute and chronic Th2-mediated lung inflammation we observed neither a pathogenic nor protective role for myeloid-expressed Arg1. The number and composition of inflammatory cells in the airways and lungs, mucus secretion, collagen deposition, airway hyper-responsiveness, and T cell cytokine production were not altered if AAMs were deficient in Arg1 or simultaneously in both Arg1 and NOS2. Our results argue that Arg1 is a general feature of alternative activation but only selectively regulates Th2 responses. Therefore, attempts to experimentally or therapeutically inhibit arginase activity in the lung should be examined with caution.